Research the causes of annular manifestations during cementing of wells production casing - Rustam Ramizovich Gasumov; Vladimir Alekseevich Gridin; Sergei Nikolaevich Ovcharov; Eldar Ramozovich Gasumov (Наука. Инновации. Технологии)
Gas migration in the annulus or gas flows between the individual formations while casing of wells during pumping of the cement slurry is a very serious problem especially for wells in inhomogeneous formations and formations with abnormally high reservoir pressures. These phenomena can occur in the annulus of wells located both on land and at sea. The possibility of gas low from the reservoir into the annulus and migrate to the annulus is due to many reasons, some of them obvious and not in doubt and the other part based on assumptions either insufficient compelling interpretations of the conducted analyses of the production material or experimental studies to some extent may be questionable. The article discussed and studied the causes and nature of annulus manifestations in various mining and geological conditions, the results of researches of inluence of various factors on the tightness of the annular space and the inluence of geological, technical, mechanical, technological and physical-chemical factors on the origin of annular manifestations is analyzed. It is defined that we should recognize the geological factor in the formation of channels in the cement stone in the process of hardening as the main factor that inluenced the occurrence of complications. Based on the results of these studies the conformity of well construction technology is assessed, a scientiically based conclusion about the reasons of the annular manifestation that occurred in the operating well after completion of cementing the production casing is composed.